우리나라 소아 알레르기비염 환자에서 호기산화질소의 측정 - 문승현; 장해지; 박윤성; 이우연; 임대현; 김정희 (Allergy asthma & respiratory disease, 2015)
Purpose: Fractional exhaled nitric oxide (FeNO) is useful for the diagnosis of allergic rhinitis (AR) as well as bronchial asthma (BA). However, FeNO may differ according to race, age, and other determinants. There have been few studies about FeNO in Korean children with AR. The aims of this study were to evaluate the value of FeNO in AR and to compare FeNO, and determinants of FeNO levels between AR, BA, and combined AR and BA. Methods: This study included 647 children aged 5 to 17. The children were classified into 5 groups after performing the skin test, FeNO measurement, the pulmonary function test, and the methacholine challenge test: those with nonallergic rhinitis (NAR), those with AR, those with BA, and those with combined AR and BA, and healthy controls,. Results: The values of FEV1 (forced expiratory volume in one second) %predicted were 94.4%±12.6%, 93.8%±20.7%, 90.0%±17.4% in AR, BA, and combined AR and BA, respectively. The values of FeNO in AR (32.3±25.0 ppb), BA (31.1±20.5 ppb), and combined AR and BA (34.5±30.4 ppb) were significantly higher compared to those of NAR (16.8±13.5 ppb) and controls (15.9±12.5 ppb). There was no significant difference in FeNO among AR, BA, and combined AR and BA. FeNO was significantly higher in patients with ≥4 positive results (36.6±29.2 ppb) than in those with <4 positive skin test results (27.6±20.7 ppb). When the receiver operating characteristic curve analysis for prediction of AR showed 0.756 of area under the curve, the cutoff level of FeNO was 16 ppb. Conclusion: In this study, children with AR had increased levels of FeNO. It is suggested that AR may have eosinophilic bronchial inflammation without BHR or clinical asthma. KCI Citation Count: 1